Relationships between maximal strength of lower limb, anthropometric characteristics and fundamental explosive performance in handball players - Hermassi, Souhail; Chelly, Mohamed Souhaiel; Wagner, Herbert; Fieseler, Georg; Schulze, Stephan; Delank, Karl-Stefan; Shephard, Roy J.; Schwesig, René (Sportverletzung · Sportschaden, 2019)
Background The purpose of this study was to examine relationships between lower body muscular strength, anthropometric characteristics and several measures of explosive performance in elite team-handball players.Methods 22 male elite team-handball players (age: 19.1 ± 1.7 years) were studied during the competitive season. Standard anthropometric and body composition measures included body mass index, lower limb and thigh muscle volume, and body fat percentage. Maximal leg strength was determined by a one-repetition maximum (1-RM) half back-squat. Vertical jump performance was assessed using a squat jump (SJ) and a counter movement jump (CMJ). Repeated shuttle-sprint ability (RSA) was tested by 6 (2 × 15 m) shuttle sprints with 20 s of active recovery intervals. The best time in a single shuttle sprint (30m; RSAbest), fastest total time (RSATT) and RSA test performance decrement (RSAdec) were recorded. Agility was measured using a modified T-half test (MAT). Throwing velocities of jump shooting and 3-step throwing were recorded by digital video camera.Results The explained variance of 1-RM half-back-squats ranged from 0.2 % (RSA% Fatigue Index) to 70.1 % (CMJ). Four out of 8 variables (RSA Best Time, CMJ, SJ, throwing velocity of jump shoot) demonstrated an r2 > 0.5. Jump performances seemed closely related to 1-RM half-back-squats. Furthermore, 1-RM half-back-squats were positively correlated with leg and thigh muscle volumes (r = 0.652, r = 0.768).Conclusion The anthropometric characteristics and some physical performance tests are closely related to the maximal strength performance of handball players. Coaches should focus on maximal strength training programs for the lower limbs when seeking improvements in the throwing velocity and jump performance of handball players.
Keywords: team-handball; maximal squat strength; explosive movement; sprint tests